Development of 5-day hikikomori intervention program for family members: A single-arm pilot trial. Issue 1 (January 2020) - Kubo, Hiroaki; Urata, Hiromi; Sakai, Motohiro; Nonaka, Shunsuke; Saito, Kazuhiko; Tateno, Masaru; Kobara, Keiji; Hashimoto, Naoki; Fujisawa, Daisuke; Suzuki, Yuriko; Otsuka, Kotaro; Kamimae, Hiroho; et al.
Abstract: Backgrounds: Hikikomori, a severe form of social withdrawal, is increasingly a serious mental health issue worldwide. Hikikomori is comorbid with various psychiatric conditions including depression, social anxiety and suicidal behaviors. Family support is encouraged as a vital first step, however evidence-based programs have yet to be established. Mental Health First Aid (MHFA) is one of the most well-validated educational programs encouraging lay people such as family members, to support close persons suffering from various psychiatric conditions such as depression, anxiety and suicidal behaviors. Methods: We newly developed an educational program for family members of hikikomori sufferers mainly based on MHFA and 'Community Reinforcement and Family Training (CRAFT)' with role-play and homework. As a single-arm trial, 21 parents (7 fathers and 14 mothers) living with hikikomori sufferers participated in our program with five once-a-week sessions (2 h per session) and six monthly follow-ups, and its effectiveness was evaluated using various self-rated questionnaires. Results: Perceived skills toward a depressed hikikomori case vignette, stigma held by participants, and subscales of two problematic and one adaptive behaviors of hikikomori sufferers were improved throughout the sessions and follow-ups. In addition, positive behavioral changes of hikikomori sufferers such as improved social participation were reported by participants. Limitations: Single-arm design and evaluation using self-rated questionnaires are the main limitations of the present study. Conclusions: Our newly developed program has positive effects on family members in their contact and support of hikikomori sufferers. Future trials with control groups are required to validate the effectiveness of this program. Abstract : Clinical psychology; Depression; Mental health; Psychiatry; Suicide; Pathological social withdrawal (hikikomori); Depression; Social anxiety; Mental health first aid (MHFA); Community reinforcement and family training (CRAFT); Family support